Gut community alterations associated with Clostridioides difficile colonization in hospitalized gastroenterological patients with or without inflammatory bowel disease - Mahnic, Aleksander; Pintar, Spela; Skok, Pavel; Rupnik, Maja (Frontiers in Microbiology, 2022)
Clostridioides difficile colonization and development of infection commonly occur in inflammatory bowel disease (IBD) patients and can trigger flare-ups. Both conditions are inherently linked to disrupted gut microbiota. This study included 149 hospitalized gastrointestinal patients, which were divided into IBD (n=48) and non-IBD patients (n=101). Patients were tested for C. difficile colonization (qPCR and selective plating), and gut bacterial communities were analyzed with 16S amplicon sequencing. Blood test results were retrospectively collected from the medical records. IBD and non-IBD patients had comparable C. difficile colonization rates (31.7% and 33.3%, respectively). Compared to non-IBD C. difficile-non-colonized patients, IBD and C. difficile-colonized patients shared multiple common bacterial community characteristics including decreased diversity and reduced abundance of strict anaerobic bacteria. Furthermore, certain microbiota alterations were enhanced when IBD was accompanied by C. difficile colonization, indicating a synergistic effect between both medical complications. Conversely, certain microbial patterns were specific to C. difficile colonization, e.g., co-occurrence with Enterococcus, which was most common in IBD patients (81.3%).